Pocket Companion to Guyton and Hall Textbook of Medical - Hall, John, 1946- (John Edward); Hall, Michael E. (Louis, Missouri : Elsevier, 2021)
Carry the same authoritative, useful knowledge that readers of Guyton and Hall have come to trust - in an easily accessible, pocket format. Pocket Companion to Guyton and Hall Textbook of Medical Physiology, 14th Edition, echoes the structure and content of the world's foremost physiology textbook, making it ideal for a quick, portable review or entry point into complex topics. Grasp key information quickly thanks to concise, readable text. Benefit from updated content of the 14th edition of the bestselling text in a condensed synopsis format. Quickly locate more in-depth discussions inside the parent text with abundant cross-references and a parallel chapter organization. Enhanced eBook version included with purchase. Your enhanced eBook allows you to access all of the text, figures, and references from the book on a variety of devices
Includes index
Keywords: Human physiology -- Handbooks, manuals, etc; Human anatomy -- Handbooks, manuals, etc; Physiology, Pathological -- Handbooks, manuals, etc